Rice Breeding in Vietnam: Retrospects, Challenges and Prospects - Tran Dang Khanh; Vu Xuan Duong; Phi Cong Nguyen; Tran Dang Xuan; Nguyen Thanh Trung; Khuat Huu Trung; Dong Huy Gioi; Nguyen Huy Hoang; Hoang-Dung Tran; Do Minh Trung; Bui Thi Thu Huong (Agriculture, 2021)
Rice breeding was conducted for a long time during historical times and is an important job in Vietnam because rice is the major food for domestic consumption and export. In this review, we have provided a comprehensive insight into the importance of promising rice germplasm resources, breeding achievements, and breeding approaches as well as discussed challenges and perspectives of rice breeding in this country. With rice germplasm and wild rice relative resources with rich and various genetic diversity, their useful genes and traits have been exploited and integrated into commercial varieties as the final outputs of rice breeding programs. New achievements of the modern genetics era have been approached and effectively contributed to breeding activities in this country. Genome sequences, molecular breeding, and mutation are powerful tools and playing vital roles in developing new varieties with characteristics of interest that should be followed by the current market demands. In the last decades, there has been a plethora of newly generated varieties by Vietnamese scientists and rice breeders and approved by the state authorities. However, very few domestic mega varieties have prevailed over the imported varieties. Therefore, rice breeding in this country is faced with big challenges, including limitations of backgrounds, budgets, and even talents in basic research to compete with other rice-producing countries. The target goals and long-term approaches for rice breeding should be paid explicitly in priority to ensure national food security and the advantage and development of rice breeding in this country.